Dark chocolate: delivery medium for probiotic Bifidobacterium breve NCIM 5671 - Sajan Chandrangadhan Achi
Bifidobacteria are widely acclaimed probiotic bacteria, however, the fragile nature of the bacteria has rendered its delivery through food products a challenge. The aim of the present study was to develop probiotic dark chocolate by incorporating Bifidobacterium breve NCIM5671. The probiotic chocolate was prepared by adding B. breve to dark chocolate at the final tempering stage. The chocolate was evaluated for the viability of B. breve upon preparation and during storage period of 90 days. The effect of addition of B. breve on physiological parameters of chocolate such as color, texture, rheology, melting profile, and sensory profile was also determined. The probiotic chocolate developed retained viability of B. breve (9 log CFU/g) for a period of 90 days. No significant differences were observed in physiological parameters of probiotic chocolate compared to control chocolate. Overall the probiotic dark chocolate was found to be a suitable matrix for delivery of B. breve NCIM5671.